Detection and Pose Adjustment in Physical Exercises using Computer Vision Techniques: Approaches, Challenges and Opportunities - Gonçalves, João; Palhares, João; Soares, Vasco N. G. J.; Neves, Paulo Alexandre (Revista de Informática Teórica e Aplicada, 2024)
In the fast-paced rhythm of modern life, the regular practice of physical exercise emerges as a source of vitality and well-being. However, it is not always feasible to practice on a gym and/or pay a personal trainer to assure a correct pose on calisthenic exercises. This article aims to investigate technological and scientific advancements in the field of computer vision to enhance exercise detection and execution, with the goal of creating a system that can be used autonomously by users. To achieve this, an introduction to the fundamental concepts inherent to the subject is provided, followed by an analysis of different technological approaches, identifying their strengths and weaknesses. Finally, the various challenges and limitations of these technologies are discussed, which remain open to be solved and explored in future research endeavors.